Analisis Maqashid Al-Syari’ah Dalam Keputusan Konsumen Memilih Hunian Islami Pada Perumahan Vila Ilhami Tangerang - Atiqi Chollisni; Kiki Damayanti (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2016)
This research aims to develop a theory of the role of theMaqashid al-Sharia as the basis for the decision of a Muslim consumers.It includes protecting religion (hifdzu-din), protecting the soul (hifdzunafs), protecting the mind (hifdzu-'aql), protecting offspring (hifdzunasl), and protecting the property (hifdzu-mal). Muslim consumers havethe advantage that they meet their needs not just to meet the individualneeds (material), but also meet social needs (spiritual). In Islam, aMuslim consumer should reflect his relationship with God (hablu minaAllah) and man (hablu mina an-nas). This concept is not found inconventional consumer behavior. This research was conducted in theresidential property industry that creates Islamic house concept. Islamichouse concept is a residential concept based on sharia law. The researchmethod used rating scale as a measure to determine the elements of themaqasid al-shariah were most responsible for Muslim consumerdecisions. The results of this study indicate that the elements of theMaqasid al-Sharia is very important, especially from the element ofprotecting religion (hifdzu-din), then protecting the property (hifdzumal), and the last is to protecting offspring (hifdzu-nasl).